Seeing the Influence of Motivation on Junior High School Students’ Learning Enthusiasm Based on Abraham Maslow’s Hierarchy of Needs Theory - Alpian Wahyudi, Muhammad (Journal of Educational Studies, 2023)
The success of the educational process can be seen from the academic and non-academic achievements of students, we can also see through evaluations per semester / semester learning outcome reports. Whether or not the values of the learning outcomes report per semester obtained are influenced by the enthusiasm of student learning which is based on the motivation of each student. Students who have a high enthusiasm for learning are definitely based on these students having good motivation as well. So the focus or purpose of this study is to investigate or see the influence of motivation on the enthusiasm for learning of junior high school students (SMP) based on Abraham Maslow's Hierarchy of Needs Theory. Data was collected through survey methods using a Likert scale questionnaire instrument distributed online via WhatsApp. The results of the analysis show a positive relationship between motivation on student enthusiasm for learning or in other words that learning motivation has a significant influence on student enthusiasm for learning. This finding has very important implications for the development of learning strategies that pay more attention or emphasis on the psychological aspects of students at the lower secondary education level or better known as junior high school.